THE ROLE OF MARKETING PERFORMANCE IN MEDIATION THE EFFECT OF ENTREPRENEURS AND THE ENVIRONMENT CHARACTERISTICS ON THE SUSTAINABILITY OF CULINARY SMEs IN SURAKARTA - Marjam Desma Rahadhini; Mutya Paramita Pratita (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
This study aims to analyze the role of marketing performance in mediating the influence of entrepreneurial characteristics and the environment on the sustainability of SMEs. SMEs are required to be able to adapt by adapting to the business environment and communicating innovative products in marketing to be able to reach consumers and reach the target market and reduce costs for business continuity. This research is survey research. The research population is culinary SMEs in the city of Surakarta. Collecting data using a questionnaire. The sampling technique used accidental sampling, as many as 96 culinary SMEs in Surakarta. Validity testing uses Confirmatory Factor Analysis (CFA), and Cronbach's Alpha for reliability testing. Data analysis using Partial Least Squares (PLS). The results showed that entrepreneurial characteristics and the business environment had an effect on business sustainability through marketing performance. Entrepreneurial characteristics and the business environment have a role in improving and marketing products and expanding the market, so that SMEs can survive and perform well during the pandemic and can increase market growth in the process of economic recoveryKeywords: entrepreneurial characteristics, business environment, marketing performance, and business sustainability